The effect of oral zinc sulfate on prevention of chemotherapy-induced oral mucositis in breast cancer patients treated with adriamycin and cyclophosphamide; a double-blind randomized clinical trial - Mahnaz Roayaei; Zeynab Andalib; Ali Akhavan (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: One of the most important complications faced by cancer patients is chemotherapy-induced oral mucositis (CIOM). In addition, the role of orally used zinc sulfate in its prevention and treatment is still a controversial issue and the results in this regard have not been conclusive. Objectives: Evaluation the effect of zinc sulfate supplement on prevention of CIOM in breast cancer patients treated with adriamycin and cyclophosphamide was the aim of this study. Patients and Methods: The current double-blind randomized clinical trial was conducted on 87 patients with breast cancer. Consumption of two oral zinc sulfate tablets and two placebo tablets with food was prescribed in the case (44 patients) and control (43 patients) groups, respectively. During the 4 cycles of chemotherapy, the incidence and severity of CIOM, the onset time of mucositis from the start of chemotherapy, the severity of pain, and the severity of dry mouth were recorded. In addition, the patients' quality of life was recorded using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Results: Findings revealed that the severity of CIOM in the first, second, and third sessions with the values of 1.22±1.01, 1.18±0.97 and 1.02±0.79, respectively, was significantly lower in the case group than the control group with the values of 1.91±0.89, 1.80±0.92, and 1.67±0.85, respectively (P<0.05). In addition, the severity of pain and dry mouth in the first and second sessions of chemotherapy was significantly lower in the case group (P<0.05). However, no significant difference was observed between the two groups in quality of life (P>0.05). Conclusion: Oral zinc sulfate had a significant role in reduction of the incidence and severity of CIOM, the severity of dry mouth, and the severity of pain in the initial sessions of chemotherapy. However, no significant difference was in postponing the incidence of CIOM and the quality of life of patients in the case group. Trial Registration: This trial protocol was approved by the Iranian Registry of Clinical Trials (identifier: IRCT20150304021338N2; https://irct.ir/trial/51105, ethical code# IR.MUI.MED. REC.1399.277).